CONSTRUCTION OF A HORSESHOE WITH POSITIVE LEBESGUE MEASURE - MENDOZA JIMENEZ, Joel (2021)
In this article, the construction of a horseshoe is studied with positive Lebesgue  measure, this horseshoe is built by analogy to the way Smale horseshoe. The difference is that the Smale horseshoe has zero Lebesgue measure introducing chaos that from the point of view probabilistic could be negligible, however when constructing the horseshoe with positive mea- sure we see that it is not.